2012
DOI: 10.1590/s0100-879x2012007500099
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of IL-1 and TNF-α polymorphisms with Helicobacter pylori in gastric diseases in a Brazilian population

Abstract: It is well known that the risk of development of gastric cancer (GC) in Helicobacter pylori -infected patients depends on several factors. Thus, the aim of this study was to investigate the effect of proinflammatory cytokine gene polymorphisms for IL-1β , IL-1RN and TNF-α on the development of GC in a Brazilian population. A total of 202 biopsies obtained from Brazilian patients with chronic gastritis and GC were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 37 publications
2
52
4
1
Order By: Relevance
“…25,26 Notably, there is considerable evidence that elevated expression of IL-1β, IFN-γ, and TNF-α are associated with chronic gastritis and gastric cancer development following HP infection. 7,11,25,27,28 Our study revealed that OPN expression was elevated in response to HP infection, and OPN depletion decreased production of these cytokines in both gastric epithelial cells and macrophages during HP infection. These results suggest that OPN is an important mediator of proinflammatory cytokine production during HP infection.…”
Section: Discussionmentioning
confidence: 58%
“…25,26 Notably, there is considerable evidence that elevated expression of IL-1β, IFN-γ, and TNF-α are associated with chronic gastritis and gastric cancer development following HP infection. 7,11,25,27,28 Our study revealed that OPN expression was elevated in response to HP infection, and OPN depletion decreased production of these cytokines in both gastric epithelial cells and macrophages during HP infection. These results suggest that OPN is an important mediator of proinflammatory cytokine production during HP infection.…”
Section: Discussionmentioning
confidence: 58%
“…Зокрема, інтерлейкін-4 (IL-4) є клю-човим медіатором Th2-типу імунної відповіді, який має протизапальні властивості, стимулює проліфе-рацію В-клітин, синтез IgE, базофілів, пригнічує синтез прозапальних цитокінів та цитотоксичність Т-клітин і макрофагів, відіграє роль при алергічному запаленні та протигельмінтному захисті [6]. Фактор некрозу пухлини альфа (TNF-) має прозапальні властивості, є важливим ендогенним пірогенним фактором, сприяє проліферації лімфоцитів, акти-вує макрофаги і натуральні кілери, сприяє синтезу прозапальних цитокінів [7,8]. Недостатньо вивчена і потребує подальшого дослідження участь паразитів в етіології та патогенезі різних захворювань травної системи.…”
Section: актуальністьunclassified
“…IL-1 is a powerful inhibitor of gastric acid secretion; on a molar basis, IL-1 is estimated to be 100-fold more potent than proton pump inhibitors and 6000-fold more potent than H 2 receptor antagonists [16,40,41]. The decrease of the acid secretion causes hypochlorhydria, which favors H. pylori infection because the secretion of acid is an important host defense mechanism against bacterial colonization in the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1, a powerful inhibitor of gastric acid secretion, is up-regulated in the presence of H. pylori and plays a major role in initiating and amplifying the inflammatory response to this infection [3,16]. Three single nucleotide polymorphisms (SNPs) associated with high levels of IL-1 secretion have been reported in the IL-1B gene: a T-C base transition at position -31 and C-T base transitions at positions -511 and +3954 from the transcriptional start site [17][18][19].…”
Section: Introductionmentioning
confidence: 99%